Hubungan Intensitas Perilaku Merokok dan Lama Merokok Dengan Indeks Massa Tubuh (IMT) - Fauziah Wahyu; Darwin Karim; Nurhannifah Rizky Tampubolon (Yayasan Jompa Research and Development, 2023)
Body Mass Index (BMI) is an important indicator of nutritional status in measuring health status. Smoking habits can have a negative impact because it can cause users to have poor nutritional status both in the form of underweight and overweight. This study aims to determine the relationship between the intensity of smoking behavior and duration of smoking with Body Mass Index (BMI). This study used a correlation descriptive design and a cross sectional approach. The research sample was 60 respondents who were taken based on inclusion criteria using total sampling technique. The analysis used was bivariate analysis using the chi-square and kolmogrov smirnov test. There were 38 respondents (63.3%) who were classified as light smokers, 47 respondents (78.3%) had habit of smoking <5 years, 28 respondents (46.7%) had normal BMI, 20 respondents had an overweight BMI, and 12 respondents had an underweight BMI. Statistical test results show that there is a significant relationship between the intensity of smoking behavior and Body Mass Index (BMI) with p value (0.043) < alpha (0.05) and there is no significant relationship between smoking duration and Body Mass Index (BMI) with p value (0.558) > alpha (0.05). The intensity of smoking behavior has a significant relationship with Body Mass Index (BMI) and duration of smoking does not have a significant relationship with Body Mass Index (BMI).